Determinants of active energy expenditure in haemodialysis patients. (25th May 2022) - Hendra, Heidy; Sridharan, Sivakumar; Farrington, Ken; Davenport, Andrew
Abstract: Background: Less active haemodialysis patients have an increased risk of mortality. We wished to determine which factors were associated with active energy expenditure (AEE). Methods: We used the validated recent physical activity questionnaire to determine AEE and estimated dietary protein intake and creatinine generation rates. We measured extracellular and total body water ratio (ECW/TBW) and appendicular lean muscle with bioimpedance and arm strength by hand grip strength (HGS). Patients were graded using the Charlson co‐morbidity and the Clinical Frailty Score (CFS). Results: AEE was calculated in 98 patients (64 male), mean age 62.1 ± 15.5 years, and AEE was negatively associated with CFS ( r  = −0.48), ECW/TBW ( r  = −0.47) and age ( r  = −0.4), all p  < 0.001, Charlson co‐morbidity score (−0.27, p  = 0.007),  and positively with serum creatinine ( r  = 0.38, p  < 0.010),  and HGS ( r  = 0.25, p  = 0.016). Although protein nitrogen accumulation and creatinine generation were associated with resting energy expenditure ( r  = 0.70 and r  = 0.44 respectively, both p  < 0.0001), neither were associated with AEE. On multivariable analysis only CFS remained independently associated with AEE ( β =  −0.031,  95% limits: −0.057 to −0.004, p  = 0.024), although both age (negative p  = 0.07), and ALM (positive p  = 0.081) were retained in the model. Conclusions: We found that AEE was lower with increasing frailty, age, loss of cell mass, co‐morbidity and inflammation, and greater AEE in patients with higher serum creatinine and albumin, and greater muscle strength on univariate analysis, but only frailty remained independently associated on multivariable analysis. Whether exercise programmes designed to increase AEE in haemodialysis patients can improve frailty scores, and so reduce mortality risk reman to be determined.